Characteristics of plasma boundaries with large density gradients and their effects on Kelvin–Helmholtz instability - Seki, K.; Matsumoto, Y.; Terada, N.; Hara, T.; Brain, D. A.; Nakagawa, H.; McFadden, J. P.; Halekas, J. S.; Ruhunusiri, S.; Mitchell, D. L.; Andersson, L.; Espley, J. R.; et al. (Frontiers in Astronomy and Space Sciences, 2024)
Boundaries between space plasmas occur in numerous contexts and scales, from astrophysical jets to planetary magnetospheres. Mass and momentum transport across the boundaries poses a fundamental problem also in the magnetospheric physics. The Kelvin-Helmholtz instability (KHI) is a promising mechanism to facilitate transport. Although previous studies have suggested KHI occurrence in various space plasmas, theory predicts that compressibility prevents KHI excitation at boundaries with large density gradient because of previously-considered boundary structures where density varies with velocity. Based on the observations of a large density gradient boundary by MAVEN at Mars, where we can observe an extreme case, here we show that it is the entropy, instead of the previously-considered density, that varies with the velocity in the real velocity-sheared boundary. The entropy-based boundary structure places the velocity shear in a lower density region than the traditional density-based structure, and weakens the compressibility effect. This new boundary structure thus enables KHI excitation even at large density gradient boundaries such as at the ionopause of unmagnetized planets and plasmapause of magnetized planets. The result suggests ubiquitous occurrence of KHI in the plasma universe and emphasizes its important role in planetary cold plasma escape from unmagnetized planets.